Studies of the laser etching on painted plastic parts to prevent the risks of engraving failures at mechatronic devices - Braga Ion Cristian; Nedelcu Anisor; Udroiu Razvan (MATEC Web of Conferences, 2017)
Nowadays, the automotive mechatronic devices are developed with many symbols engraved over the painted plastic parts. Many risks are coming due to painting layer, which could be dry or not, the paint thickness variability it is also one important aspect. The paper’s aim is to present the studies of the laser etching process and the risk reduction of the possible failure by using the 2D optical measurement of different parameters for the laser beam, also using the 3D scanning in order to see the deep etching of the paint. The experiments will let the team know what should be the parameter setting for the painted plastic materials delivered in production in different time after the painting, therefore to reduce the over-adjusting and first part approval process duration.